Recent Progress on Stability of Layered Double Hydroxide-Based Catalysts for Oxygen Evolution Reaction - Lielie He; Yangen Zhou; Mengran Wang; Simin Li; Yanqing Lai (Nanomaterials)
Water electrolysis is regarded as one of the most viable technologies for the generation of green hydrogen. Nevertheless, the anodic oxygen evolution reaction (OER) constitutes a substantial obstacle to the large-scale deployment of this technology, due to the considerable overpotential resulting from the retardation kinetics associated with the OER. The development of low-cost, high-activity, and long-lasting OER catalysts has emerged as a pivotal research area. Layered double hydroxides (LDHs) have garnered significant attention due to their suitability for use with base metals, which are cost-effective and exhibit enhanced activity. However, the current performance of LDHs OER catalysts is still far from meeting the demands of industrial applications, particularly in terms of their long-term stability. In this review, we provide an overview of the causes for the deactivation of LDHs OER catalysts and present an analysis of the various mechanisms employed to improve the stability of these catalysts, including the synthesis of LDH ultrathin nanosheets, adjustment of components and doping, dissolution and redeposition, defect creation and corrosion, and utilization of advanced carbon materials.